DEMOCRACY AND GENDER EQUALITY - Beer, Caroline (Jurnal Ilmiah Peuradeun, 2015)
This article examines the relationship between democracy and gender equality. In particular, it contrasts the impact of long-term stocks of democracy with the contemporary level of democracy and the participation of women in democracy. It contends that democracy should be thought of as a historical phenomenon with consequences that develop over many years and decades and that women’s participation should be included as an important component of democracy. The main argument is that long-term democracy together with women’s suffrage should provide new opportunities for women to promote their interests through mobilization and elections. A cross-national time-series statistical analysis finds that countries with greater stocks of democracy and longer experience of women’s suffrage have a higher proportion of the population that is female, a greater ratio of female life expectancy to male life expectancy, lower fertility rates, and higher rates of female labor force participation.